Considerations on exclusivity clauses - Chirieac Roxana Maria, (Technium Social Sciences Journal, 2020)
In the context of internet sales can we still speak about a traditional exclusivity clause inserted in commercial contracts? As a market development, we can see that even without the COVID 19 pandemic, Internet sales were boosted all over the world. With international actors such as Amazon, JD.com Inc., E-bay or Apple as well as many others, we have seen ecommerce sale rise up to 3.46 trillion US dollars in 2019 alone. Even if these sales only amount to 16.4% of global sales, according to digital commerce specialists, the numbers will be much higher during and post pandemic. This being said, is there any place left for traditional exclusivity clauses inserted in many commercial contracts such as franchise, distribution or agency contracts? What will happen with specific clauses that grant one of the parties the right to an exclusive use of a territory or the right to address a certain population? During the years, doctrine as well as jurisprudence has shown that exclusivity clauses must be drafted with balance; the risk is huge in the sense that it might restrict the free access to the market, offer clients products that are of lesser quality or lead to a stranglehold of the market. On the other hand, the use of contracts that contain exclusivity clauses might become irrelevant for the beneficiary as they will no longer offer the protection and specific interest. The study aims to analyse exclusivity clauses as defined in the national and international regulations as well as study the current framework and the jurisprudence’s position on exclusivity clauses, especially the ones related to e-commerce.